Perspectives on The Piloting of Climate Information Services and Climate Smart Agricultural Innovations Under The AICCRA Project in Five Selected Agro-Ecological Zones of Ghana - Honger, Joseph; Gariba, Awudu Amadu; Osae, Michael; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The AICCRA project, led by IITA recently introduced some climate smart Agricultural Innovations and Climate information services to help improve upon the farming activities and livelihoods of farmers in some selected communities in Ghana. Innovations such as the use of improved seeds, proper soil and nutrient management practices and integration of climatic data into decision making were introduced to farmers in five agro-ecological zones cutting across six regions in Ghana. To assess perspectives of stakeholders (farmers, Agricultural extension agents and District directors of Agriculture) involved in the projects, series of meetings were held with representatives of these stakeholders, to obtain first-hand information. A questionnaire was designed and used to collect qualitative data from the respondents. Key questions sought to assess the understanding of the introduced technology to farmers, its relevance to the farmers and whether stakeholders have some suggestions for improving the project in subsequent years. Generally, all farmers demonstrated good understanding of the technologies demonstrated and many had begun implementing some in their own farms and were unanimous in their assertion that the introduced technologies gave superior yields compared to their traditional practices. The responses from farmers were corroborated by their District Directors and Extension Agents involved in the project. Stakeholders unanimously suggested that the climate information services introduced by the project must be sustained and that tractor services and the improved seeds introduced by the project must be made available to the farmers and that they were ready to acquire these at a fee. In the Guinea and Sudan Savannah zones, stakeholders suggested that groundnut, must be introduced in subsequent years to improve the participation of women.